2012
DOI: 10.4172/1948-5956.1000147
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Mesothelioma of Peritoneum: About a Case with Review of the Literature

Abstract: Malignant mesothelioma of the peritoneum is rather unusual and is only 10-20% of malignant mesothelioma. Malignant mesothelioma is pleural recognized by its location. The etiology of malignant mesothelioma is in 80% of cases prior contact with asbestos but there are cases without specific cause. The prognosis for MPM is poor with median survival of 5.4 months versus 12.5 months for pleural mesothelioma. The diagnosis of MPM is often difficult and requires surgical biopsies by laparoscopy or laparotomy or ascit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Peritoneal mesothelioma is a rare tumor characterized by diffuse or locoregional involvement of peritoneal surfaces. In industrialized countries, the incidence is currently estimated to be between 0.5-3 cases per million for men, and 0.2-2 cases per million for women [4]. Currently, no biomarkers have been identified for use in the diagnosis and/or to follow-up of this entity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peritoneal mesothelioma is a rare tumor characterized by diffuse or locoregional involvement of peritoneal surfaces. In industrialized countries, the incidence is currently estimated to be between 0.5-3 cases per million for men, and 0.2-2 cases per million for women [4]. Currently, no biomarkers have been identified for use in the diagnosis and/or to follow-up of this entity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in their report concerning 201 cancer patients including four cases with malignant mesothelioma, Zimmerman et al, reported that serous effusions from two out of four mesothelioma patients (50%) and twenty-eight patients out of forty-four adenocarcinoma patients (64%) stained positive for hCG and mucin. They concluded that β-hCG was not clinically useful for effusion cytology because of a low specificity [7]. In another study by Ugurman et al, pleural and serum β-hCG levels and their ratio were evaluated for discriminating benign and malignant pleural effusions.…”
Section: Discussionmentioning
confidence: 99%